Contribution of mental flexibility in strengthening cultural identity - atamnia, fateh; sayhi, salima (Journal of Social Sciences and Humanities, 2023)
The current study aimed to talk and stand on the contribution of mental flexibility in strengthening cultural identity. Given the importance of mental flexibility as a way of life and way of thinking and its contribution to maintaining and strengthening cultural identity and as a willingness and cognitive skill in the development and development of self-efficacy and as one of the modern variables in the field of positive psychology After reviewing the theoretical heritage by the researcher, the concept of cultural identity and mental flexibility was addressed, and then touched on the extent of the contribution of mental flexibility in strengthening cultural identity. The intervention concluded with a set of recommendations and suggestions.